Investigations on the preparation of ceramsite from petrochemical excess sludge - Liu, Zhengwei; Zhang, Hai; Lin, Xiaoyu; Zhang, Hongzhe; Zhang, Zhiyuan; Zhang, Shucai (Frontiers in Chemistry, 2022)
The petrochemical excess sludge, as a hazardous solid waste, poses a great threat to the environment and is difficult to dispose in an economic and environmentally-friendly way. A new method is proposed to use the petrochemical excess sludge to prepare the ceramsite. The relationship between the sintering behavior of dried excess sludge including the composition, temperature, fluxing agent and pore-forming agent addition and the properties of the ceramsite is investigated. The properties of the ceramsite are primarily affected by the sintering temperature and the addition of fluxing agent. The ceramstie with a sintering-expanded surface is prepared. And its water absorption is quite low, indicating an improvement of densification due to sintering. Moreover, the leaching toxicity of the heavy metals in the dried excess sludge and prepared ceramsite is also investigated. It reveals the feasibility of the ceramsite preparation by sintering petrochemical excess sludge.